0818 Sleep and ADHD in Children: Are Pediatric Residents Considering Sleep Problems When Diagnosing ADHD?. (27th April 2018) - Reinecke, K; Vaughn, B; Fan, Z; Perry, M; Roth, H
Abstract: Introduction: The purpose of this study is to determine whether pediatric residents consider sleep problems when assessing patients with hyperactivity and inattention. The symptoms of Attention Deficit/Hyperactivity Disorder (ADHD) are also often seen in sleep disorders such as obstructive sleep apnea (OSA) and restless leg syndrome (RLS). The commonly used NICHQ Vanderbilt Assessment Scale does not screen for sleep problems; therefore, the sleep evaluation must be in the interview, exam, and diagnostic testing. The hypothesis is that residents may not adequately assess sleep prior to diagnosing ADHD, which may be due to limited education about sleep. Methods: Pediatric residents at two large academic institutions were surveyed using the online Qualtrics platform. The survey asked about the diagnostic approach to ADHD, including typical screening questionnaires, differential diagnosis, physical exam components, and testing. Questions were also included about the diagnostic approach to sleep problems, as well as barriers that interfere with evaluation of sleep. Results were compared using standard descriptive statistics. Results: Thirty questionnaires were returned, with 28 completed. All residents used the Vanderbilt scale; residents were aware that sleep problems were not included in this questionnaire. Although 52% considered sleep problems in the top 5 differential diagnoses, only 28% routinely screened for OSA, and only 7% routinely screened for RLS. The pharynx, which may reveal tonsillar enlargement concerning for OSA, was ranked in the top 3 most important physical exam components by only 25%. The 3 most frequently endorsed barriers to screening for sleep problems were lack of training (86%), lack of time (71%), and lack of access to questionnaires (54%); lack of time was most frequently chosen as the most significant. Conclusion: Although about half of pediatric residents consider sleep an important component of the differential diagnosis for ADHD, only a minority screened for the treatable sleep disorders of RLS and OSA. Assessment for sleep disorders in patients with hyperactivity and inattention might be improved with more resident education as well as increased access to tools that expedite screening for sleep disorders. Support (If Any):